NANCE AND MOYERS ANALYSIS STUDY ON MEASUREMENT OF AVAILABLE SPACE IN THE MANDIBULAR DENTAL ARCH - DBU, Amalia; Sutjiati, Rina; DAP, Leliana Sandra (Fakultas Kedokteran Gigi Universitas Jember, 2012)
The shape and size of dental arch plays an important role in determining the space available for teeth. To avoid crowding the teeth it needs the space provided (available space) is sufficient for the permanent teeth grow. Measurement of available space on the discrepancies in the diagnosis of orthodontic models generally use the analysis Moyers and the analysis Nance. The research was carried out by casting the lower jaw in 30 subjects. The cast is then measured using a brass wire available space on the analysis of Nance and digital calipers on the analysis of Moyers. The data obtained were then conducted a t test with a significance of p <0.05 to determine differences in measurement results available space mandibular dental arch based on the analysis Moyers and the analysis Nance. The test results obtained by using t test p value of 0.563 (p> 0.05). The resulting value shows that the size of the available space in the mandibular dental arch analysis Moyers and analysis Nance showed no significant difference, so that the analysis can be used to measure the available space mandibular dental arch in the permanent dentition.